Finding Order in Chaos: A Review of Hospital Ratings. (March 2016) - Hwang, Wenke; Derk, Jordan; LaClair, Michelle; Paz, Harold
Publicly reported hospital performance data have become widely available to health care consumers in recent years. In response to a growing demand for more readily available health care information, various organizations have begun assessing hospital performance. These performance reporting systems have tremendous potential to aid patients, families, and primary care providers in their clinical decision making. This study takes a systematic approach to review the main features of 9 existing hospital rating systems, each of which is described using 9 areas of evaluation. The hospital rating systems included in this study vary widely in scope, methodology, transparency, and presentation of their results. Their results often present conflicting conclusions regarding the performance of the same hospital. This review of hospital rating systems demonstrates how public reporting may add confusion to patients' health care decision making.